Functional evolutions for homogeneous stationary death-immigration spatial dynamics - Finkelshtein, D. L. (Methods of Functional Analysis and Topology, 2011)
We discover death-immigration non-equilibrium stochastic dynamics in the continuum also known as the Surgailis process. Explicit expression for the correlation functions is presented. Dynamics of states and their generating functionals are studied. Ergodic properties for the evolutions are considered.